Pengaruh Rendam Kaki Dengan Air Hangat Terhadap Penurunan Tekanan Darah Pada Lansia Hipertensi Di Puskesmas Engkeran Kecamatan Lawe Alas Kabupaten Aceh Tenggara - Aryani, Novita; Sisca Dwi Ningsih; Muhammad Syahbirin (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Hypertension is a systolic blood pressure of more than 140 mmHg and a diastolic of more than 90 mmHg. In addition to pharmacological therapy, the management of hypertension can use nonpharmacological therapy, one of which is soaking foot therapy with warm water. This study aims to determine the effect of foot baths with warm water on reducing blood pressure in hypertensive elderly in Pusker Engkeran in 2019. This type of research is a quasi-experimental design with one-group pre and post test design, the sampling technique of this study uses purposive sampling with the number of samples was 40 respondents. data collection techniques in this study used an observation sheet. From the results of paired t test showed that there was a significant influence between before and after therapy soak feet with warm water. The results of pre and post soaking feet with warm water were obtained p-value = 0.000 (<0.05). This is the influence before and after warm water soak therapy to reduce blood pressure in hypertensive elderly. Suggestions: this research is expected to be a frame of reference and reference for further research regarding therapeutic therapy for reducing blood pressure in the elderly and also adding other variables not yet discussed in this study, in order to improve further research.